Cyst in the pulp of an intact human immature tooth: Case report - Vojinović Jovan; Vojinović Olivera; Vučetić Mirjana (Serbian Medical Society - Dental Section, Belgrade, 2004)
The aim of this paper was to histologically present and analyze a cyst in the pulp of an intact human immature tooth as a rare case in dental practice. The cyst was discovered in the left upper first premolar of a 9 year old following tooth extraction for orthodontic reasons. Presence of this cyst in an immature tooth may impair the pulp integrity and the tooth on the whole, so early and adequate diagnosis is essential.